Sifat Biologi Tanah Pada Lahan Aplikasi dan Tanpa Aplikasi Tandan Kosong Kelapa Sawit di Adolina PT. Perkebunan Nusantara IV - Sakiah Sakiah; Ade Firmansyah; Dina Arfianti (Jurnal Penelitian Pertanian Terapan, 2020)
Oil palm empty fruit bunches (OPEFB) is one of the solid wastes from the processing of palm oil into crude palm oil. Generally, OPEFB is used as mulch on oil palm plantations. This study aims to compare the soil biological properties on land with the application of OPEFB and land without the application of OPEFB in a depth of 0-20 cm and 20-40 cm. Soil sampling was carried out at Adolina, PT Perkebunan Nusantara IV, in block 06 A (land with the application of OPEFB) and block 06 B (land without the application of OPEFB). The observation parameters are organic matter content, total microbes, and soil respiration. Then, the data analysis results are processed with SPSS version 20. The test was using a t-test. The research results of oil palm empty fruit bunches application with a dose of 35 tons ha-1 which were applied evenly without layering on the oil palm plantations aged 13 years can increased soil organic matter content at a depth of 0-20 cm but does not increase total microbes and soil respiration both at a depth of 0-20 cm and at a depth of 20-40 cm compared with total microbes and soil respiration on land without the application of OPEFB.